Pengembangan Media SUMPING (SUpport SuaMi PendamPING) untuk Mengukur Kemandirian Suami dalam Mendampingi Persalinan - Rahmadona Rahmadona; Utami Dewi; Nurniati Tianastia Rullyni; Heriza Syam; Kartika Sri Dewi Batubara (Universitas Faletehan, 2025)
More than 90% of maternal deaths are caused by complications that often occur during or around childbirth. Reducing the incidence of childbirth complications requires the active participation of the family, especially the husband. The study aims to find out the use of e-modules and SUMPING videos on the independence of husbands in childbirth assistance. Observational descriptive research with a comparative design of these two groups was carried out on 100 husbands who were divided into groups e module SUMPING and video SUMPING of each 50 person. Data were collected at Midwifery Independent Practice Sites in Tanjungpinang and Bekasi City using questionnaires and observation sheets. Data were processed and analyzed using the chi-square test and Fisher's exact test. The results showed that the variables of education, exposure to information, experience, knowledge, and motivation had a significant effect (p-value <0.05) on the independence of husbands in group e modules and videos, but had no effect on the variables of age and occupation (p-value > 0.05). The results of this study conclude that independence in childbirth assistance can be increased by increasing knowledge and motivation supported by higher education background, information exposure, and experience in childbirth assistance. The use of e-modules and SUMPING videos can be recommended for husbands to increase their independence in providing childbirth assistance.